The girls : a novel - Cline, Emma (New York : Random House, 2016)
Mesmerized by a band of girls in the park she perceives as enjoying a life of free and careless abandon, 1960s teen Evie Boyd becomes obsessed with gaining acceptance into their circle, only to find herself drawn into a cult and seduced by its charismatic leader.
Keywords: Teenage girls -- Fiction; Communal living -- California -- Fiction; Nineteen sixties -- Fiction; Counterculture -- Fiction; Psychological fiction